Assessing the Role of AI Chatbots in Enhancing Arabic and English Learning within Kuwait’s Bilingual Education System (The Science Post, 2026)
The bilingual education system, where Arabic and English are used throughout the primary, secondary, and highereducation in Kuwait, is the key to achieving both global competence and cultural and linguistic identity. Although thissystem has strengths, it has issues to do with the lack of individualized language use, limited classroom time, and lackof feedback opportunities, especially when it comes to second language acquisition. The recent developments in thesphere of artificial intelligence (AI), namely chatbots driven by AI, offer some perspective of overcoming thesedrawbacks, through adaptive, interactive, and learner-driven language assistance. This paper evaluates the use of AIchatbots in improving the acquisition of both Arabic and English languages in Kuwait, which has a bilingualeducation system. Based on the available literature and the contextual analysis, the study examines the way AIchatbots can facilitate personal practice, learner autonomy, and the development of listening, speaking, reading, andwriting skills in a balanced manner. Also, the paper considers the pedagogical advantages, practical issues, andgeneral implications of inclusion of chatbot technologies, paying specific focus to technological preparedness, theviews of educators, and the student involvement and achievement. The results are expected to be useful in the contextof making informed choices about the successful implementation of AI chatbots in the bilingual education system andin the context of the creation of supportive, inclusive, and culturally sensitive language learning experiences inKuwait.